Serotonergic mechanism of the lateral parabrachial nucleus and relaxin-induced sodium intake - Menani, José Vanderlei [UNESP]; Barbosa, S. P.; McKinley, M. J.; Wade, J. D.; De Luca, L. A. (Elsevier B.V., 2004)
It has been shown that central or peripheral injections of the peptide relaxin induces water intake, not sodium intake in rats. Important inhibitory mechanisms involving serotonin and other neurotransmitters in the control of water and NaCl intake have been demonstrated in the lateral parabrachial nucleus (LPBN). In the present Study, we investigated the effects of bilateral injections of methysergide (serotonergic receptor antagonist) into the LPBN on intracerebroventricular (i.c.v.) relaxin-induced water and NaCl intake in rats. Additionally, the effect of the blockade of central angiotensin AT(1) receptors with i.c.v. losartan on relaxin-induced water and NaCl intake in rats treated with methysergide into the LPBN was also investigated. Male Holtzman rats with cannulas implanted into the lateral ventricle (LV) and bilaterally in the LPBN were used. Intracerebroventricular injections of relaxin (500 ng/l mul) induced water intake (5.1+/-0.7 ml/120 min), but not significant 1.8% NaCl intake (0.5+/-0.4 ml/120 min). Bilateral injections of methysergide (4 mug/0.2 mul) into the LPBN strongly stimulated relaxin-induced 1.8% NaCl intake (34.5+/-10.9 ml/120 min) and slightly increased water intake (10.5+/-4.9 ml/120 min). The pretreatment with i.c.v. losartan (100 mug/l mul) abolished the effects of i.c.v. relaxin combined with LPBN methysergide on 1.8% NaCI intake (0.5+/-0.4 ml/120 min). Losartan (100 mug/l mul) also abolished relaxin-induced water intake in rats injected with methysergide into the LPBN (1.6+/-0.8 ml/120 min) or not (0.5+/-0.3 ml/120 min). Losartan (50 mug/l mul) partially reduced the effects of relaxin. The results show that central relaxin interacting with central angiotensinergic mechanisms induces NaCl intake after the blockade of LPBN serotonergic mechanisms. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: angiotensin; sodium appetite; thirst; serotonin; relaxin